1990
DOI: 10.21273/hortsci.25.3.330
|View full text |Cite
|
Sign up to set email alerts
|

Growing Conditions Alter the Relationship Between SPAD-501 Values and Apple Leaf Chlorophyll

Abstract: The relationship between SPAD-501 meter readings (SPAD) and total chlorophyll content (TCHL) was evaluated for `Delicious' apple (Malus domestica Borkh.) leaves grown in various environments. Regression models were developed between SPAD and TCHL for each of six separate experiments and were evaluated for statistical coincidence. SPAD was linearly related in a positive manner to TCHL in five of the six experiments; however, models differed between experiments, particularly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…These inconsistencies led to the poor relationship between SPAD and chlorophyll data. Campbell et al (1990) showed that growing conditions affect the relationship of SPAD readings to total chlorophyll, due in part to differences in leaf morphology. In a recent study, SPAD readings were highly correlated to total chlorophyll levels and visual observations of color for greenhouse grown st. augustinegrass, but correlated poorly in field grown plants due to a lack of uniformity in ontogenetic age of the samples and sampling error (Rodriguez and Miller, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies led to the poor relationship between SPAD and chlorophyll data. Campbell et al (1990) showed that growing conditions affect the relationship of SPAD readings to total chlorophyll, due in part to differences in leaf morphology. In a recent study, SPAD readings were highly correlated to total chlorophyll levels and visual observations of color for greenhouse grown st. augustinegrass, but correlated poorly in field grown plants due to a lack of uniformity in ontogenetic age of the samples and sampling error (Rodriguez and Miller, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In July and August, herbicide treatment did not affect leaf greenness compared with the control. Although the SPAD meter is a useful instrument for nondestructive determination of total chlorophyll content, on broadleaf plants, it has limitations (i.e., requirement for multiple measurements, influence of leaf thickness) (Campbell et al, 1990;Chapman and Barreto, 1997). SPAD measurements of leaf greenness are not useful for quantifying herbicide injury on oak seedlings.…”
Section: Swollen Budmentioning
confidence: 99%
“…The ability to determine chlorophyll content on a leaf-area basis using SPAD values was demonstrated for apple {Mains domestica Borkh.) (CAMPBELL et al 1990), cotton (Gossypium hirsutum L.) (WOOD et al 1992b), grape {Vitis vinifera L.) (FANIZZA et al 1991), maize (Zea mays L.) (DWYER et al 1991, PlE-KIELEK and FOX 1992, SCHEPERS et al 1992, WoODetal. 1992a, pepper {Capsicum annuum L.) (HARTZ et al 1993), potato {Solarium tuberosum L.) (VOS and BOM 1993), sorghum {Sorghum bicolor (L.) Moench) (MARQUARD and TiPTON 1987), soybean {Glycine max (L.) Merr.)…”
Section: Introductionmentioning
confidence: 99%